Assessment of Elementary School Teachers’ Level of Knowledge and Attitude regarding Traumatic Dental Injuries in the United Arab Emirates - Manal A. Awad; Eman AlHammadi; Mariam Malalla; Zainab Maklai; Aisha Tariq; Badria Al-Ali; Alaa Al Jameel; Hisham El Batawi (International Journal of Dentistry)
Introduction. In this cross-sectional study, the level of knowledge and attitude of elementary school teachers regarding traumatic dental injuries (TDI) were assessed. Materials and Methods. A questionnaire was distributed to 330 elementary school teachers in 30 randomly selected schools in the Emirates of Sharjah and Dubai. The questionnaire collected information on participants’ demographic characteristics, first aid training, and attitude about emergency management of TDI. Results. 292 teachers (88%) completed the questionnaires; of these, 95% were females, and 50% of the participants had first aid training. Knowledge about tooth avulsion was inadequate, and first aid training was not associated with correct responses to management of avulsed teeth (p>0.05). A significantly higher percentage of younger teachers (p<0.05) expressed the need for future education on TDI management. A significantly higher percentage of participants who had an educational position (95%) indicated that they did not have enough knowledge regarding TDI compared to physical education teachers (79%) and administrators (87%) (p<0.05). Conclusions. Elementary school teachers in the UAE have a low level of knowledge regarding the management of dental trauma. Educational programs that address TDI are needed and could improve the elementary school teachers’ level of knowledge in emergency management of TDI.